2021
DOI: 10.1088/1755-1315/805/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Status of small-scale tuna fisheries at Haruo Village, Central Maluku Regency

Abstract: The Haruo Village is one of the villages situated in Central Maluku Regency. This village is one of the most populous villages that have the livelihood of being tuna fishermen. All the fishermen from this village are considered mostly small-scale fishermen. The study was conducted between July to September 2020 to assess the sustainability of small-scale tuna fishery and proposed sustainable management strategy. Rapfish analysis was used to analyze small-scale tuna sustainability status and DPSIR to proposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The information confirms that tuna fisheries are a potential and profitable resource that drives people in many countries to exploit the fish extensively. Some studies have revealed a decrease in tuna fiaheries in some areas [28,29,30]. Based on the potency of tuna fishery as a driving force and the tuna fishermen as a pressure , then conceptual model based on DPSIR was consructed to propose a management strategy for sustainable small-scale tuna fishery (Figure 4).…”
Section: Management Strategy For Sustainability Of Small-scale Tuna F...mentioning
confidence: 99%
See 1 more Smart Citation
“…The information confirms that tuna fisheries are a potential and profitable resource that drives people in many countries to exploit the fish extensively. Some studies have revealed a decrease in tuna fiaheries in some areas [28,29,30]. Based on the potency of tuna fishery as a driving force and the tuna fishermen as a pressure , then conceptual model based on DPSIR was consructed to propose a management strategy for sustainable small-scale tuna fishery (Figure 4).…”
Section: Management Strategy For Sustainability Of Small-scale Tuna F...mentioning
confidence: 99%
“…This could be done through an international organization to ensure better conservation management and to achieve sustainable management of that fishery [2,3]. 1207 (2023) 012001 IOP Publishing doi:10.1088/1755-1315/1207/1/012001 2 Indonesian tuna fishery gives a quite considerable contribution to the fishing industry of Indonesia as well as to world fisheries [4]. The tuna resources are still under high pressure on a global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the problems mentioned above, this study aims to determine the sustainability status of small-scale fisheries (below 10 GT) after the reclamation closure in Jakarta Bay. Parameters involved in determining the sustainability status are taken from multiple dimensions such as capture fisheries resources, economy, ecology or environment, social, legal and institutional (Fauzi andAnna 2002, 2005;Nababan et al 2007;Fauzi 2019;Tetelepta et al 2021). In the after reclamation sustainability analysis, the RAPFISH (rapid appraisal for Fisheries) model was developed by a team from the University of British Columbia and FAO (Pitcher 1999;Pitcher and Preikshot 2001;Anna 2003;Kavanagh and Pitcher 2004;Anna and Fauzi 2007;Fauzi 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the after reclamation sustainability analysis, the RAPFISH (rapid appraisal for Fisheries) model was developed by a team from the University of British Columbia and FAO (Pitcher 1999;Pitcher and Preikshot 2001;Anna 2003;Kavanagh and Pitcher 2004;Anna and Fauzi 2007;Fauzi 2019). Fisheries management in Indonesia using RAPFISH has been carried out by various methods, such as the sustainability status of smallscale tuna fisheries (Tetelepta et al 2021), sustainability study of household-scale fisheries (Hartati et al 2021), sustainability status for reef fisheries management (Kurnia et al 2021), sustainability status for hammerhead shark (Anna et al 2020), sustainability status of fisheries in the vicinity of tin mining area (Ramadona et al 2020). This method is not only used in Indonesia, but other countries as well, such as Iran (Allahyari 2010), India (Adiga et al 2015), Brazil (Jimenez et al 2021), and Chile (Milagros et al 2021).…”
Section: Introductionmentioning
confidence: 99%